Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.orglett.5b00281
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Enantioselective Catalytic Monoepoxidation of Conjugated Dienes: Synthesis of Chiral Allylic cis-Epoxides

Abstract: Ti(IV)-salan 4 catalyzes the diastereo- and enantioselective monoepoxidation of conjugated dienes using 30% H2O2 at rt or below even in the presence of other olefins and adjacent stereocenters. Its enantiomer, ent-4, provides access to the opposite diastereomer or enantiomer. The resultant chiral allylic epoxides, and the triols derived from them, are versatile synthetic intermediates as well as substructures present in many bioactive natural products. The epoxidation is highly specific for Z-olefins. For 1-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 70 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…In other words, allylic hydroxyl groups may coordinate to the Nb anion in some forms first. To the best of our knowledge, in other catalytic systems such as methyltrioxorhenium (MTO), , dimethyl dioxirane (DMD), m -chloroperbenzoic acid ( m -CPBA), POMs, W complexes, ,, and Ti–substrate systems, two interaction forms, such as hydrogen bonds and metal–alcoholate bonds, have been postulated. Consequently, here we have systematically investigated the epoxidation process of allylic alcohols by [Nb­(O-O) 2 (OOH) 2 ] − in hydrogen bonding and metal–alcoholate bonding mechanisms, respectively, aiming to shed light on the favored reaction mechanism and demonstrate the catalytic activity from a theoretical perspective.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In other words, allylic hydroxyl groups may coordinate to the Nb anion in some forms first. To the best of our knowledge, in other catalytic systems such as methyltrioxorhenium (MTO), , dimethyl dioxirane (DMD), m -chloroperbenzoic acid ( m -CPBA), POMs, W complexes, ,, and Ti–substrate systems, two interaction forms, such as hydrogen bonds and metal–alcoholate bonds, have been postulated. Consequently, here we have systematically investigated the epoxidation process of allylic alcohols by [Nb­(O-O) 2 (OOH) 2 ] − in hydrogen bonding and metal–alcoholate bonding mechanisms, respectively, aiming to shed light on the favored reaction mechanism and demonstrate the catalytic activity from a theoretical perspective.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The same catalyst 41 also catalyzed the epoxidation of a series of ( Z )-enol esters to afford the epoxides in high yield with high enantioselectivity ranging from 86 to >99% ee . It is worth noting that catalyst 43a /Ti­(O i Pr) 4 (5 mol %) was found to efficiently conduct the monoepoxidation of conjugated dienes, affording the corresponding chiral allylic cis -epoxides (19 examples) with 72–98% ee …”
Section: Asymmetric Epoxidation Reactionsmentioning
confidence: 99%
“…Recently, Falck and co‐workers reported that Ti–salan complex 7 is able to catalyze distal selective epoxidation of conjugated dienes even in the presence of other olefins and adjacent stereocenters (Scheme ) . In this context, a variety of well‐established methods for asymmetric epoxidation were surveyed for the regioselective epoxidation of conjugated dienes.…”
Section: Metal‐catalyzed Asymmetric Epoxidation Using Hydrogen Peroxmentioning
confidence: 99%